AMAR: (Sobre)vivências de pós-graduandos e egressos LGBTQIA+ em Educação Matemática - João Gabriel Souza Freitas (2025)
The present study seeks to identify relationships between gender, sexuality, and Mathematics Education to understand how prejudice, stigma, and bullying have affected/affect LGBTQIA+ graduate students and/or alumni in Mathematics Education. To achieve this purpose, we will use the Narrative Research methodology, working with experiences, life stories, and memories without being bound to specific configurations of (re)telling a story. From this perspective, (auto)biographical narratives will be used, as we understand that they open diverse possibilities for capturing oral accounts while also addressing aspects of memory, recollection, and experience, allowing the author to position themselves as a narrator as well. Thus, in our analyses, we chose to construct an (auto)biographical narrative of the author, approaching, from an intersectional perspective, key themes highlighted by the research participants to make visible dissident experiences outside the cisheteronormative framework. In conclusion, we observed how these processes of violence influence the lives of LGBTQIA+ individuals, marking them for the rest of their lives and highlighting the urgent need for their presence in society to disrupt the norm and advocate for equitable rights that respect diversity. We also recognized the importance of these narratives in fostering a more inclusive and welcoming academic environment.